Indeks Massa Tubuh sebagai Prediktor Performa pada Atlet Akuatik - Gafur Ammar Santoso; R. Boyke Mulyana; Novrizal Achmad Novan; Syifa F. Sihab; Fikri Rizkia (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2026)
This study aimed to examine the validity of Body Mass Index (BMI) as a predictor of performance in aquatic athletes based on the Multistage Shuttle Swim Test (MSST). An ex post facto research design with a correlational approach was employed. The participants consisted of 66 national and regional-level aquatic athletes from West Java Province, representing swimming, water polo, and finswimming. BMI was measured using the Tanita Body Composition Analyzer 360, while performance was assessed using the MSST. Data were analyzed using Pearson correlation as well as non-parametric Kendall’s tau-b and Spearman’s rho tests with a significance level set at p < 0.05. The results indicated no significant correlation between BMI and MSST performance (r = 0.136; p = 0.276). These findings confirm that BMI is not a valid predictor of performance in aquatic athletes.